2019
DOI: 10.3390/nu11112627
|View full text |Cite
|
Sign up to set email alerts
|

Compliance and Adherence to Enteral Nutrition Treatment in Adults: A Systematic Review

Abstract: Objective: To review the scientific literature that has verified and/or assessed compliance and adherence to enteral nutrition (EN) in adult patients. Method: This study involved a critical analysis of articles retrieved from MEDLINE (PubMed), The Cochrane Library, Embase, Scopus and Web of Science using the terms “Treatment Adherence and Compliance” and “Enteral Nutrition”, applying the filters “Comparative Study” or “Clinical Trial”, “Humans” and “Adults”. Date of the search: 25 October 2018. Results: A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 55 publications
3
14
0
9
Order By: Relevance
“…A further limitation of the present study is that adherence was measured based on ‘honesty recall’ rather than a biological marker of nutrition intake. This is a known limitation of many dietary intervention studies and the methods used to assess adherence in the present study are consistent with other research on EEN or PEN treatments ( 22,23 ) . Moreover, conscientiousness was self‐reported, although self‐report is used routinely in personality psychology.…”
Section: Discussionsupporting
confidence: 88%
“…A further limitation of the present study is that adherence was measured based on ‘honesty recall’ rather than a biological marker of nutrition intake. This is a known limitation of many dietary intervention studies and the methods used to assess adherence in the present study are consistent with other research on EEN or PEN treatments ( 22,23 ) . Moreover, conscientiousness was self‐reported, although self‐report is used routinely in personality psychology.…”
Section: Discussionsupporting
confidence: 88%
“…Por otro lado, las bases de datos de Scopus y Web of Science recuperaron muchos trabajos que finalmente fueron irrelevantes, lo que podría deberse a la falta de indexación (la búsqueda se realizó en formato de texto consultando el título, el resumen y las palabras clave) y la imposibilidad de limitar la búsqueda por tipo de artículo (restringido a ensayos clínicos). Este alto "ruido" de documentos también se observó en otras recientes revisiones sistemáticas (33,34).…”
Section: Discussionunclassified
“…Hosp Domic. 2020;4(1):[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Artículos de revisión: Álvarez Velásquez S, Sanz Valero J Al evaluar la calidad de los artículos seleccionados para la revisión, mediante el cuestionario CONSORT, las puntuaciones oscilaron entre mínimo de 11 (44% de cumplimiento) y máximo de 19,50 (78% de cumplimiento), con mediana igual a 13,5 (tabla 2).Los documentos revisados se publicaron en diferentes países, siendo Alemania el país que aportó un mayor número de referencias, con 4 (26,7%) estudios en total(15,16,20,23). Además, los 15 (100%) artículos incluidos en la tabla de la revisión estaban redactados en inglés (9-23).El estudio de Atzpodien et al(16), de 2002, presentó la población con el mínimo de edad, 57 años, y el de Tassinari et al(13), de 2007, incluyó la población con la edad máxima de 72 años.La patología estudiada en todos los estudios fue la neoplasia, siendo la más prevalente la metastásica(13,19,20,23).El periodo de tratamiento de los documentos revisados presentó un mínimo de 21 días (22) y un máximo de 21 meses(16).…”
unclassified
“…Measurement of adherence in clinical nutrition studies is challenging, specifically for outpatients because they may not report their real intake, either influenced by negligence or by lack of understanding of the importance of surveillance. 25,27,28 Two of three studies that performed analyses comparing adherent to non-adherent patients, reported better outcomes in patients who accomplished the nutrition intervention. Most studies did not examine the impact of adherence and non-adherence on outcomes.…”
Section: Discussionmentioning
confidence: 99%